Porous coal char-based catalyst from coal gangue and lignite with high metal contents in the catalytic cracking of biomass tar. (15th June 2022) - Du, Shilin; Shu, Rui; Guo, Feiqiang; Mao, Songbo; Bai, Jiaming; Qian, Lin; Xin, Chengyun
Abstract: In this study, coal gangue and lignite with high metals-containing are used to prepare porous coal char-based catalysts for biomass tar decomposition via a simple pyrolysis method under CO2 atmosphere. The CO2 etching during the preparation process of the catalysts helps to improve the porosity of the coal char, and the metals in coal are exposed on the surface of the catalyst, thus enhancing the adsorption of the catalysts to the reactants and contact possibility of the reactants with the metals. The activity of the catalysts is influenced by the metals content and preparation temperature, and the coal gangue char prepared at 800 °C (CG-800) exhibits the highest catalytic activity in this work. At a reforming temperature of 700 °C, the conversion efficiency of biomass pyrolysis tar reaches 91.2% using CG-800 as the catalyst with a high total syngas yield of 516 mL/g. Moreover, part of the metal oxides in the catalysts can be reduced by the reducing gases during the tar reforming process, which can further help the catalysts maintain high catalytic activity in the recycling process. During the five-time reuse, the catalysts exhibit excellent stability with only a slight loss in tar conversion and total gas yield. Graphical abstract: Image 1 Highlights: Porous char catalysts were prepared from coal gangue and lignite for biomass tar cracking. The activity of catalysts is related to metal content and preparation temperature. The tar conversion efficiency reached 91.2% at 700 °C using CG-800 catalyst. The coal char-based catalysts maintained good stability in the five-cycle test.